Educational reforms in India for the 21st century - Aggarwal, J C (Delhi Shipra, 2000)
Educational reforms in India for the 21st century providing an analytical view of the efforts made in India and abroad to revitalise education so as to meet the challengesof 21st century. Educational policies and comprehensive bibliography of national lev
Keywords: Educational change-India; Educational planning-India